Intraspecies and interspecies transmission of mink H9N2 influenza virus - Zhao Yong-feng (Nature Portfolio, 2017)
Abstract H9N2 influenza A virus (IAV) causes low pathogenic respiratory disease and infects a wide range of hosts. In this study, six IAVs were isolated from mink and identified as H9N2 IAV. Sequence analysis revealed that the six isolates continued to evolve, and their PB2 genes shared high nucleotide sequence identity with H7N9 IAV. The six isolates contained an amino acid motif PSRSSR↓GL at the hemagglutinin cleavage site, which is a characteristic of low pathogenic influenza viruses. A serosurvey demonstrated that H9N2 IAV had spread widely in mink and was prevalent in foxes and raccoon dogs. Transmission experiments showed that close contact between H9N2-infected mink and naive mink, foxes and raccoon dogs resulted in spread of the virus to the contact animals. Furthermore, H9N2 challenge experiments in foxes and raccoon dogs showed that H9N2 IAV could infect these hosts. Virological and epidemiological surveillance of H9N2 IAV should be strengthened for the fur animal industry.